2016
DOI: 10.1007/s10717-016-9788-9
|View full text |Cite
|
Sign up to set email alerts
|

Action of the Products of Biofuel Combustion on the Phase Composition and Structure of Refractory Material

Abstract: The changes occurring in the phase composition and microstructure of aluminum-silicate refractory material which disintegrated during operation in a solid-biofuel combustion unit were investigated. The main reasons for the disintegration of the material were determined on the basis of investigations performed by using modern methods and analyzing the results in comparison with published data on the chemical composition of volatile products of biofuel combustion and their physical-chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
2
Order By: Relevance
“… 37 The reaction of alkali metals with silicon and aluminum oxides might have occurred via aerosol collisions prior to deposition on superheater surfaces and, subsequently, within the refractory materials ( reaction R14 ). 38 …”
Section: Resultsmentioning
confidence: 99%
“… 37 The reaction of alkali metals with silicon and aluminum oxides might have occurred via aerosol collisions prior to deposition on superheater surfaces and, subsequently, within the refractory materials ( reaction R14 ). 38 …”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that when excessive CO has been formed in the boiler for extended periods (disrupted boiler operational mode), disintegration of refractory castable with high iron oxide content (>4.4%) due to the general effect of CO and alkali occurred already after 8 months of operation ( Figure 6) [15]. Risks of refractories degradation due to CO can be reduced by using materials with as low amount of Fe 2 O 3 as possible (<1%).…”
Section: Resistance To the Impact Of Carbon Monoxide (Co)mentioning
confidence: 99%
“…Cracking (a) and degradation of aluminosilicate materials due to the formation of new compounds (carbon and leucite) in its structure (b)[15].…”
mentioning
confidence: 99%
“…Основной недостаток такого бетонаего низкие механические свойства после обжига при 800-1100 о С (например, предел прочности при сжатии < 20 МПа). Прочность традиционного жаростойкого бетона можно улучшить, модифицируя его состав ультрадисперсной добавкой микрокремнезема и дефлокулянта [1] [3,6]). Дополнительный негативный фактортермические напряжения в материале из-за частых остановок -пусков энергетических котлов для их очистки от золы и шлаков.…”
Section: Introductionunclassified
“…П. Зданявичус 1 , д. т. н. В. Антонович 1 , д. т. н. Р. Борис 1 , д. т. н. Р. Стонис 1 ( ) , д. т. н. Р. Шукис 2 , д. т. н. Е. Витек 3 1 Институт строительных материалов, Вильнюсский технический университет им. Гедиминаса…”
unclassified